The contribution of serum cortisone and glucocorticoid metabolites to detrimental bone health in patients receiving hydrocortisone therapy - Rosemary Dineen; Lucy-Ann Behan; Grainne Kelleher; Mark J. Hannon; Jennifer J. Brady; Bairbre Rogers; Brian G. Keevil; William Tormey; Diarmuid Smith; Christopher J. Thompson; Malachi J. McKenna; Wiebke Arlt; et al. (BMC Endocrine Disorders, 2020)
Abstract Background Glucocorticoid therapy is the most common cause of iatrogenic osteoporosis. Less is known regarding the effect of glucocorticoids when used as replacement therapy on bone remodelling in patients with adrenal insufficiency. Enhanced intracellular conversion of inactive cortisone to active cortisol, by 11 beta-hydroxysteroid dehydrogenase type 1(11β-HSD1) and other enzymes leading to alterations in glucocorticoid metabolism, may contribute to a deleterious effect on bone health in this patient group. Methods Study design: An open crossover prospective study randomizing ten hypopituitary men, with severe ACTH deficiency, to three commonly used hydrocortisone dose regimens. Measurements: Following 6 weeks of each regimen, patients underwent 24-h serum cortisol/cortisone sampling, measurement of bone turnover markers, and a 24-h urine collection for measurement of urinary steroid metabolites by gas chromatography-mass spectrometry (GC-MS). Serum cortisone and cortisol were analysed by liquid chromatography-mass spectrometry (LC-MS). Results Dose-related and circadian variations in serum cortisone were seen to parallel those for cortisol, indicating conversion of ingested hydrocortisone to cortisone. The median area under the curve (AUC) of serum cortisone was significantly higher in patients on dose A (20 mg/10 mg) [670.5 (IQR 621–809.2)] compared to those on dose C (10 mg/5 mg) [562.8 (IQR 520.1–619.6), p = 0.01]. A negative correlation was observed between serum cortisone and bone formation markers, OC [1–49] (r = − 0.42, p = 0.03), and PINP (r = − 0.49, p = 0.01). There was a negative correlation between the AUC of night-time serum cortisone levels with the bone formation marker, OC [1–49] (r = − 0.41, p = 0.03) but there were no significant correlations between day-time serum cortisone or cortisol with bone turnover markers. There was a negative correlation between total urinary cortisol metabolites and the bone formation markers, PINP (r = − 0.39, p = 0.04), and OC [1–49] (r = − 0.35, p = 0.06). Conclusion Serum cortisol and cortisone and total urinary corticosteroid metabolites are negatively associated with bone turnover markers in patients receiving replacement doses of hydrocortisone, with nocturnal glucocorticoid exposure having a potentially greater influence on bone turnover. Trial registration Irish Medicines Board Clinical Trial Number – CT900/459/1 and EudraCT Number – 2007-005018-37 . Registration date: 07-09-2007.